Using econometrically-estimated import demand systems to analyze domestic and international issues: a case study of Saudi Arabian agricultural imports - Al-Sultan, Mahdi M., author; Davies, Stephen P., advisor; Thilmany, Dawn D., committee member; Pritchett, James G., committee member; Fan, Laing-Shing, committee member (Colorado State University. Libraries, 2002)
With dramatically growing food consumption, combined with the country's climatic conditions and water scarcity, Saudi Arabia depends heavily on food imports to cover the gap between domestic demand and local production. This increasing reliance on imports, along with expected effects of the World Trade Organization (WTO) negotiations on agriculture, and declining domestic production due to changes in domestic policy are the main problems facing the Saudi agricultural sector. This suggests the need to evaluate effects of domestic and international policy change on imports, local production and local demand for key products in the sector. The objectives of this research are, first, to empirically analyze the demand for food imports using recent methodological developments in the implementation of demand systems. Then, these estimated demand parameters are utilized to analyze domestic and international policy issues. To attain these objectives, a demand system for imports was estimated using several systems (Rotterdam, AID S, CBS, and NBR), which are all nested alternatives in a general model, and then expenditure and price elasticities were calculated. The CBS model was found to be the best model for analyzing import behavior in this study, and it was used to compute expenditure elasticities, own-price elasticities, and cross price elasticities. The estimated expenditure elasticities imply that if aggregate consumer expenditure allocated to agricultural imports was to increase, the demand for imports would increase. Also, prices show unitary elasticities for six of eight categories. In order to link domestic and international effects across a variety of alternatives, a restricted regression using the CBS import model was developed to estimate domestic demand elasticities in the presence of alternative supply elasticities. With these matrices of elasticities in hand, a policy analysis framework was developed and simulations of three different issues were made. The first simulation deals with the effect of world price increases from WTO effects, and most import quantities are seen to decline, with the highest decrease for vegetables and fruit (72 percent). There is also an increased incentive for local production, as for example, feed grains expand by 46 percent in response to the WTO price increases. The second simulation deals with the impact on domestic supply due to changes in input prices (water and a subsidy on imported live animals). The results show declining local production because of increasing input prices, with the greatest decline in feed grains (45.5 percent). The reduction in production varies according to input supply elasticities, output supply elasticities, and the local production share in domestic demand. The third simulation shows the effect of increased expenditures on imported goods. The results differ between groups depending on expenditure elasticities and a group's import share in local demand. Once again, feed grains show the highest response (18 percent).
Keywords: agriculture; studies; agricultural production; natural resources; restrictions; population growth; objectives; expenditures; simulation; cooperation; groundwater; migration; planning; wheat; dairy products; barley